The Doubleday atlas of the United States of America - Bacon, Josephine (New York : Doubleday, 1990)
An introduction to the United States including relief and position maps, geographical features, population, major cities, state capitals, major economic activities, and other information about each state.
Includes index.
Keywords: United States -- Maps; United States -- Maps